Effects of Bio Stimulants on Growth, Yield and Quality of Tomato - Mollick, Sourav; Karak, Chandan; Roy, Biplab; Chakraborty, Biswajit; Das, Puspita; Bhutia, Pradeep (International Journal of Economic Plants, 2024)
The field experiment was carried out at Central Research Farm, Gayeshpur, BCKV, Nadia, West Bengal, India during the Rabi season (October, 2021 to March, 2022) with the aim to study the effects of different biostimulants for growth, yield and quality of tomato. The treatments were T1 (Control or untreated), T2 (Bayfolan Algae @ 1.5 ml l-1), T3 (Bayfolan Algae @ 2 ml l-1), T4 (Bayfolan Algae @ 2.5 ml l-1), T5 (Isabion @2 ml l-1), T6 (Bayfolan Algae @ 5 ml l-1) and T7 (Isabion @ 1.5 ml l-1). Analysis of variance clearly revealed the significant effects of biostimulants with different treatments in respect to growth, yield and quality parameters of tomato. The treatment T4 (Bayfolan Algae @ 2.5 ml l-1) recorded significantly maximum plant height (82.47 cm), number of branches plant-1 (7.04) at 60 DAT, fruit weight (74.63 g), maximum average yield plant-1 (3.26 kg, yield plot-1 (130.18 kg) and yield ha-1 (872.32 q). The same treatment T4 of Bayfolan Algae @2.5 ml l-1 also recorded maximum equatorial diameter (6.92 cm), maximum polar diameter (5.80 cm) and highest values of TSS (5.08 °brix), highest lycopene (5.05 mg 10-1) and ascorbic acid (26.74 mg g-1) content even which is economically viable and emerged as best treatment for getting better growth, yield and quality of Tomato.